2016
DOI: 10.1155/2016/2124638
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Clinical Application of Tetramethylpyrazine (an Interesting Natural Compound Isolated from Ligusticum Wallichii): Current Status and Perspective

Abstract: Tetramethylpyrazine, a natural compound from Ligusticum wallichii (Chuan Xiong), has been extensively used in China for cardiovascular and cerebrovascular diseases for about 40 years. Because of its effectiveness in multisystems, especially in cardiovascular, its pharmacological action, clinical application, and the structural modification have attracted broad attention. In this paper its mechanisms of action, the clinical status, and synthetic derivatives will be reviewed briefly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 80 publications
1
67
0
1
Order By: Relevance
“…In past, a traditional Chinese herbal medicine, Ligusticum wallichii (family Umbelliferae), is commonly used with other herbs to provide therapeutic intervention in cardiovascular and neurovascular disorders as this herb has an intense ability to repress the muscle contractions and low systemic blood pressure [12]. The new function of L. wallichii is capable of protecting host cells against hypoxia-induced injury likely through improving the antioxidant status and immunity profile [13][14][15]. Since the high inter-relationship between inflammation and hypoxia, we presume that L. wallichii may also be benefit for the cells upon OA inflammatory condition.…”
Section: Introductionmentioning
confidence: 99%
“…In past, a traditional Chinese herbal medicine, Ligusticum wallichii (family Umbelliferae), is commonly used with other herbs to provide therapeutic intervention in cardiovascular and neurovascular disorders as this herb has an intense ability to repress the muscle contractions and low systemic blood pressure [12]. The new function of L. wallichii is capable of protecting host cells against hypoxia-induced injury likely through improving the antioxidant status and immunity profile [13][14][15]. Since the high inter-relationship between inflammation and hypoxia, we presume that L. wallichii may also be benefit for the cells upon OA inflammatory condition.…”
Section: Introductionmentioning
confidence: 99%
“…The MH_Daqu of GujingTribute does contain Bacillus licheniformis, but this strain only occupies 0.68% in all MH_Daqu bacteria, while in Maotai Daqu Bacillus licheniformis is the most dominant species. This may explains why Maotai has a higher concentration of TTMP than other types of liquor [22][23].…”
Section: Relationship Between Daqu and Liquor Aroma Molecules'originmentioning
confidence: 97%
“…For example, Bacillus licheniformis is one of the tetramethylpyrazine (TTMP) -producing microorganisms [20], and TTMP is a both aroma and health-benefiting chemical [21][22], so it is expected that GujingTribute liquor has a higher concentration of it by increasing the amount of TTMP-producing strains. The MH_Daqu of GujingTribute does contain Bacillus licheniformis, but this strain only occupies 0.68% in all MH_Daqu bacteria, while in Maotai Daqu Bacillus licheniformis is the most dominant species.…”
Section: Relationship Between Daqu and Liquor Aroma Molecules'originmentioning
confidence: 99%
“…Chuanxiong Rhizoma is one of these TCM which was usually used in the treatment of brain and heart diseases [5] in the past. Isolated from the alkaloid extracted from Chuanxiong Rhizoma, tetramethylpyrazine has multiple pharmacological effects including anti-oxidation, improving microcirculation, and inhibition the production of glycation [6]. Current studies have also revealed that Chuanxiong Rhizoma could inhibit endothelial cell damage [7], as well as vascular smooth muscle cell proliferation [8].…”
Section: Introductionmentioning
confidence: 99%